(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Each element functions as an independent technical object (TO) performing a specific function and facilitating a specific physical process (FJ). This leads to the emergence of two types of connections between elements and, accordingly, two types of systemic management. These elements have specific functional relationships, forming a constructive-functional structure (CFS). The CFS is built based on the correspondence of the function and structure of TOs. This article presents scientific research on methods for improving the CFS of the sprinkler device.